Pengaruh Online Customer Review dan Online Customer Rating terhadap Purchase Decision dengan Trust sebagai Variabel Intervening pada Pengguna Aplikasi Shopee Semarang - Usman Usman; Alifah Ratnawati (Lembaga Yasin AlSys, 2026)
Although the development of e-commerce has encouraged consumers to increasingly rely on online customer reviews and online customer ratings before making purchases, previous research findings still show inconsistencies regarding the effects of these two variables on purchase decisions, particularly through trust as a mediating variable. This study aims to analyze the effect of online customer reviews and online customer ratings on purchase decisions, with trust as a mediating variable among Shopee users in Semarang City. This study used a quantitative approach with a purposive sampling technique involving 100 respondents who had made purchases through Shopee. Data were collected through a questionnaire and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS. The results showed that online customer reviews had no significant effect on trust but had a positive and significant effect on purchase decisions. Conversely, online customer ratings had a positive and significant effect on trust but had no direct effect on purchase decisions. In addition, trust had a positive effect on purchase decisions and was unable to mediate the effect of online customer reviews on purchase decisions, but was able to mediate the effect of online customer ratings on purchase decisions. The conclusion of this study confirms that Shopee users’ purchase decisions in Semarang City are more directly influenced by the quality of customer reviews, whereas ratings play a role in building trust, which subsequently encourages purchase decisions. These findings provide practical implications for platform managers and online business actors to enhance the credibility of reviews and strengthen rating mechanisms as a basis for building consumer trust.